Wasiat Kepada Non Muslim Perspektif Hukum Keluarga Islam - Jaya Putra, Marwan; Putra, Marwan Jaya; Ja'far, A. Kumedi (Laskar Karya, 2024)
This study discusses the law of bequests to non-Muslims within the context of Islamic family law and positive law in Indonesia. The background of this issue arises from the tension between the Sharia provisions that do not allow inheritance among individuals of different religions and the needs of an increasingly inclusive multicultural society. The aim of this writing is to explore the perspectives of Islamic law and positive law regarding bequests, as well as their social and ethical implications. The research method used is a literature review and comparative analysis between the two legal systems, focusing on legal texts, scholarly fatwas, and court decisions. The research findings indicate that, although Islamic law has strict limitations on inheritance for non-Muslims, there is room for bequests that can be executed as a legal instrument. On the other hand, positive law in Indonesia, through the practice of mandatory bequests, recognizes the rights of non-Muslim heirs, thus creating equality in the distribution of inheritance. The conclusion of this study emphasizes the necessity for open dialogue and a deeper understanding of the interaction between the two legal systems. This is crucial to reduce potential conflicts and ensure justice and inclusivity in inheritance practices within a diverse society.